MBELAJARAN FIQIH MTs DI JOMBANG (Analisis Penerapan Metode Metode Diskusi Terhadap Kemandirian Belajar Siswa) - Ainiyah, Qurrotul; Maulana, Handika (ILJ: Islamic Learning Journal, 2023)
Penelitian ini bertujuan untuk mengetahui efektivitas metode stract: This study aims to determine the effectiveness of the discussion method on student independence in MTs Miftahul Ulum Distance Kulon Jogoroto. This type of qualitative research with a descriptive approach. Data collection techniques are carried out by observation, interview documentation. The results showed the effectiveness of the discussion method on student independence in learning fiqh class VIII at MTs Miftahul Ulum Jogoroto. Overall it went well and smoothly. In its application there are three stages, namely giving assignments, carrying out tasks and being accountable or evaluating. The constraints experienced in applying the Effectiveness of the Discussion Method to Students' Independence in Class VIII Fiqih Learning at MTs Miftahul Ulum Jogoroto are technical and non-technical. Efforts are made to overcome the obstacles that occur in the application, never mind the maximum, including the teacher and the students themselves. Efforts made include giving directions and questions to fifth grade students, in order to explore understanding and increase student learning independence, the teacher packs the Discussion method well into the lecture and question and answer method without reducing the initial purpose of applying the Discussion method and finally students are given an understanding of the importance of learning Fiqh